Business-to-business marketing - Brennan, Ross (Sage, 2014)
This text covers both the theory and practice of business-to-business (B2B) marketing from a European perspective in a globalised world. This edition includes: More coverage of digital marketing and social media in relation to B2B ; More coverage of issues relating to sustainability and corporate social responsibility ; More visual features and an update of the B2B Snapshots ; New international examples and case studies including Zara, eBay, DHL, LinkedIn, and the horsemeat scandal ; Includes more extensive online resources including full lecturer materials and further materials for students including web links, links to SAGE journal articles, exam questions and a quizes. The text is relevant to all students taking a university module in B2B marketing at undergraduate or postgraduate levels. It will also be relevant to researchers and practitioners in the area of B2B marketing.